Masa Orientasi dan Penyesuaian Diri Mahasiswa Baru - Astrini Astrini (Bina Nusantara University, 2011)
Students as individuals who experience molding of young people in a university are the expectations and support the nation in order to continue development for the welfare of the nation. Achievements that can exceed the standard of education and are also able to develop themselves in order to face numerous challenges effectively represents hope for all students. In order to meet the expectations carried by students, an orientation program should be considered for starting freshman at the university. Usually conducted in both local and overseas universities are the orientation program for new students which aims to introduce students to the campus. Stage of development of students as well as those aspects of life that affect him on the lecture adjustments need to be a basis for making orientation program for new students. This will make the orientation program not only as recognition programs and additional insight into the world but also makes the campus orientation program as a program that facilitates the adjustment of students to be able to meet the needs and meet the demands and expectations as a student. Effective adjustment will occur if the existing orientation program can serve to facilitate and support students in adjusting themselves in the lectures.